THE EFFECT OF COMBUSTION TEMPERATURE IN THE MAKING OF BIOBRIQUETTE FROM THE SKIN OF PEANUT - Komala, Ria (KINETIKA, 2017)
Energy consumption will continue to increase in the coming years. While the national energy reserves will be depleted if no new energy reserves are found. One of the renewable energy that has great potential in Indonesia is biomass. The biomass can be processed into biobriquette, which is a fuel with a high level of heat value. The skin of peanut is one of the household industrial waste that has energy value. The skin of peanut contains a lot of cellulose, so it can be used as briquette fuel. In this study, the independent variables used were carbonization temperatures, ranging from 3000C, 3500C, 4000C, 4500C, 5000C, 5500C. While the fixed variable is carbonization time for 5 minutes, and the composition used is 90 grams of charcoal and 10 grams of adhesive starch solution. From the research, briquettes have optimum quality with carbonization temperature of 450 0C with heating value of 6795 cal / gr, moisture content of 7.28%, ash content of 8.21%, levels of flying substances 19.12%, and carbon content solid 65.39%.